Wound assessment and patients' knowledge of wound care at a rural community health centre in the Bojanala district, Rustenburg - Mokgethi, Millicent Johannah (My University, 2019)
Purpose of the study: The study sought to establish, describe the types and status of managed wounds, as well as the patient knowledge regarding factors that had an impact on wound healing in a rural community healthcare centre in Bojanala District, Rustenburg. Methods: A cross sectional descriptive and correlational design was applied. The anticipated sample was 105 (n=105), however the Bates-Jensen Wounds Assessment Tool (BWAT) was used for data collection on a conveniently realised sample of 93 (n=93) participants. Descriptive data analysis of the participants’ demographic data, types and status of wounds was conducted. In addition, multi linear regression analysis was used to determine the correlation between age, lifestyle habits and the presence of chronic disease with wound healing. Furthermore, quantitative data analysis was used to analyse participants’ knowledge on wound care and healing. Results: The response rate was 88.6% (n=93). A total of 122 wounds were assessed, of which 78.5% presented with only one wound. The findings revealed eight different wound types, with acute wounds being the most prevalent (79.6%). Of the wounds assessed, 31.2% were trauma wound types affecting predominantly 55.2% males and 44.8% females; the majority of wounds were small, not more than 4sq cm. The prevalence of pressure ulcers was only 4.30% with the sacrum being the common area mostly affected; a bloody type of exudate was noted in 40.9% of the participants. The majority of participants in the current study reported good lifestyle habits, as manifested by 70% and 75.3% respectively, not indulgent in alcohol or smoking habits. The results showed that hypertension, followed by HIV were the common chronic diseases affecting participants (34.4% and 18.7% respectively), with very few (37.6%) taking prescribed medications. Multi linear regression established a statistical significance in the scores of age (p>0.025), type of wound (p>0.002) and duration of wounds (p>0.001), predicting wound healing. Regarding knowledge of wound care, 70% of the participants responded correctly to wound healing questions, despite their poor level of education. The common wound care practice of cleaning wounds was salted water, used by the majority (57.1%) of participants. Unsatisfactory and not evidence-based practices were noted in very few (10.2 %) participants. Recommendations: Some of the recommendations from this study were firstly to develop a research-based pre-test and post-test training programme on nurses’ knowledge of wound assessment criteria and process; secondly, development of a research-based pilot project of wound intervention strategy for patients with chronic wounds; thirdly, to develop guidelines for strengthening of infection control policies as the researcher has observed the nonexistence of policy guidelines on wound management in the district where the study was conducted. Conclusion: The participants were predominantly males. The majority of participants reported a good lifestyle neither smoking nor using alcohol, whilst a minority of slightly more than 30% reported having chronic diseases. The most common reported chronic disease in this study was hypertension. Most of the participants presented with one wound and the lower leg category seemed to be the most common area afflicted. The findings furthermore showed a statistical significance in the scores of age (p>0.025), type of wound (p>0.002) and duration of wounds (p>0.001), predicting wound healing. In addition, the results showed that almost
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2019